PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL INKUIRI TERBIMBING BERBANTUAN ETNOID (ETNOSAINS ANDROID) PADA MATERI GETARAN DAN GELOMBANG - Faudina Permatasari; Madlazim Madlazim; Wahono Widodo (Jurnal Pembelajaran Sains, 2019)
The aim of this study is to develop learning devices with Etnoid assisted guided inquiry models in eighth-grade students at Semester II in Ngunut 2 Junior High School in Tulungagung. This research a  in two stages, namely the preparation stage which aims to develop the device followed by the implementation stage of learning in the classroom using the pretest-posttest design. The validation test consisted of media validation tests by media expert lecturers from the Chemistry Department and the material validation test by material experts from the Science Study Program lecturers. The learning phase was carried out by involving 30 eighth grade students at Ngunut 2 Junior High School who had taken the material of vibration and waves. The results of the development are in the form of learning tools with the Etnoid assisted guided inquiry model. The result of the validity value of 93.88% is a very valid category, the practicality value of 86.70% is a very practical category, and the effectiveness value is 0.703 high category information is very effective to use in learning. Based on the results of the data analysis, it can categories that the learning device with the Etnoid assisted guided inquiry model which has been developed has met very decent criteria. So, it can improve students' high-level thinking skills.